1996
DOI: 10.1021/bi9606509
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the H+/e- Stoichiometry in Mitochondrial Cytochrome c Oxidase:  Influence of the Rate of Electron Flow and Transmembrane ΔpH

Abstract: A study is presented of the factors affecting the H+/e- stoichiometry of the proton pump of mitochondrial cytochrome c oxidase, isolated and reconstituted in phospholipid vesicles (COV). Under level flow conditions, i.e., in the absence of a transmembrane delta muH+, the H+/e- ratio, obtained from spectrophotometric measurements of the initial rates of electron flow and H+ release specifically elicited by cytochrome c, varied from around 0 to 1, depending on the actual rate of electron flow through the oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 53 publications
1
56
1
Order By: Relevance
“…However, the structure is expected to facilitate a strictly controlled ET from Cyt c to CcO, which is crucial for efficient energy transduction by CcO, because each ET to CcO is coupled with pumping of one proton equivalent (26). In fact, it has been shown that the energy coupling efficiency (H þ ∕e − stoichiometry) is sensitively influenced by the electron flow rate and provides a maximum efficiency at a moderate flow rate (27).…”
Section: Comparisons Of the Present Results With Other Electron Transmentioning
confidence: 99%
“…However, the structure is expected to facilitate a strictly controlled ET from Cyt c to CcO, which is crucial for efficient energy transduction by CcO, because each ET to CcO is coupled with pumping of one proton equivalent (26). In fact, it has been shown that the energy coupling efficiency (H þ ∕e − stoichiometry) is sensitively influenced by the electron flow rate and provides a maximum efficiency at a moderate flow rate (27).…”
Section: Comparisons Of the Present Results With Other Electron Transmentioning
confidence: 99%
“…These results suggest that oxidation state of heme a influences the decay rate without affecting the O 2 reduction mechanism. On the other hand it has been reported that an appropriate overall electrontransfer rate is required in order to obtain the maximal protonpumping efficiency (H þ ∕e − ) (27). Therefore, the fully reduced CcO is unlikely to provide the maximal proton-pumping efficiency upon oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The observed non-linearity of the steady-state relationship between respiratory rate and vp is taken by some authors as evidence of slip in proton pumps [19], by others as due to non-ohmic increases of membrane proton conductance at high vp (leak) [20]. Papa et al have carried out an extensive study of the in£u-ence of kinetic and thermodynamic factors on the H /e 3 stoichiometry of cytochrome c oxidase in mitochondria and in the isolated-reconstituted state (COV) [17,18,21]. The results of the investigations, based on measurement of the rates of electron £ow and proton ejection at level £ow, showed that the H /e 3 ratio of proton pumping by the oxidase varies, both in intact mitochondria and in the isolated-reconstituted oxidase, from around zero, at extremes of low and high rates, to about one at intermediate rates (see also [14]).…”
Section: Features Of the Proton Pump In Cytochrome C Oxidasementioning
confidence: 99%